Application of expiratory flow increased technique in the respiratory therapy of premature neonates: a systematic review - Kosiorowska, Anna; Kołodziejczyk-Nowotarska, Alicja; Bokiniec, Renata (Pediatria Polska - Polish Journal of Paediatrics, 2026)
Expiratory flow increased technique (EFIT) in respiratory therapy is a treatment strategy for neonates in neonatology departments. The purpose of this study was to present the current understanding of the application of the EFIT in respiratory therapy for premature neonates. The first part describes an overview of the literature on EFIT. PubMed, Medline, Embase, Scopus, and Google Scholar databases were searched for trial studies on EFIT therapy in infants published from January 2020 to September 2024. The second part presents the EFIT technique for newborns, along with its indications and contraindications. There were 5 papers concerning the respiratory therapy of neonates and related solely to EFIT. Literature shows that EFIT therapy improves the respiratory parameters. The knowledge and experience that has been gained concerning the impact of therapy on the respiratory system of premature neonates encourages the use of the EFIT therapy in neonatology.